PEMBENAHAN WEB PROFIL SINODE GEREJA KRISTEN JAWA - Budi Susanto; Laurentius Kuncoro Probo Saputra (Institute of Research and Community Outreach - Petra Christian University, 2020)
The GKJ Synod Web had undergone several modifications independently. It led to a vulnerability condition that cost system breaches. Building the web application independently in limited security resource was the main problem for GKJ Synod. In order to resolve the problem, the GKJ Synod collaborated with FTI UKDW. Wordpress was implemented to restore the the GKJ Synod web. The restoration process, requirement and content analysis, and information architecture design. Based on the information architecture design, the website had been setup and then the team empowered the Data and Multimedia Information Service Center of GKJ Synod to maintain the web application and the contents. The installed WordPress utilised the VPS service with an additional SSL security protocol that provides development support and security. Thie web application project will continue to the next stage which is online document management services.